Holy Hatred - Michael, R. author. aut Link
IX, 254 p.
Keywords: Although Christianity's precise influence on the Holocaust cannot be determined and the Christian churches did not themselves perpetrate the Final Solution, Michael argues that two millennia of Christian ideas and prejudices and their impact on Christians' behaviour appear to be the major basis of antisemitism and it's apex, the Holocaust.